2022
DOI: 10.3390/en15155590
|View full text |Cite
|
Sign up to set email alerts
|

Home Energy Upgrades as a Pathway to Home Decarbonization in the US: A Literature Review

Abstract: This work aims to characterize how home energy upgrade projects and programs in the US have evolved over the past decade. It also identifies what changes are needed to drive expansion of the US energy retrofit market in such a way that addresses carbon emissions from buildings, improves resilience and upgrades the housing stock. This review focuses on whole-home energy upgrades, targeting deep energy retrofit savings of >30%. The topics we cover include trends in home electrification, US and European home e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Panel and service upgrades are another potentially significant cost to homeowners wishing to electrify. Cost data is scarce in academic literature, and past studies have shown a wide variance in actual cost [4]. The total cost (labor and materials) of replacing an electrical panel averages $2,989 over four sources of data.…”
Section: Cost Of Electrical Infrastructurementioning
confidence: 99%
“…Panel and service upgrades are another potentially significant cost to homeowners wishing to electrify. Cost data is scarce in academic literature, and past studies have shown a wide variance in actual cost [4]. The total cost (labor and materials) of replacing an electrical panel averages $2,989 over four sources of data.…”
Section: Cost Of Electrical Infrastructurementioning
confidence: 99%
“…They analysed only energy efficiency solutions and not energy saving ones. Other authors [11] described how home energy upgrade projects and programs in the US have evolved in the past decade, with the aim of achieving significant energy retrofit savings greater than 30%.…”
Section: Background Scope and Novelty Of The Studymentioning
confidence: 99%